Perilaku Konsumsi Dalam Perspektif Ekonomi Islam: Studi Kasus Mahasantri Putri Pondok Pesantren Tarbiyatut Tholabah Kranji Paciran Lamongan - Siti Nur Jami’uswaniyah; Eny Latifah (Universitas Dian Nuswantoro, 2022)
This study aims to find about: (1) the consumption behavior of female female student at the Tarbiyatut Tholabah Islamic Boarding School Kranji Paciran Lamongan, (2) an Islamic economic perspective on the consumption behavior of female female student at the Tarbiyatut Tholabah Islamic Boarding School Kranji Paciran Lamongan. This research method used is qualitative with the type of study research case. To collect data is done by interview, observation and documentation. The results of this study are: (1) consumption behavior of female student of the Tarbiyatut Tholabah Islamic Boarding School in consuming an item prioritizes want over needs., (2) the consumption behavior of female female student at the Tarbiyatut Tholabah Islamic Boarding School is not yet in accordance with Islamic economic principles related to the principles simplicity.